THE RELATIONSHIP BETWEEN MOTHER'S KNOWLEDGE AND HANDLING OF DIARRHEA IN TODDLERS IN TANJUNG BALAI CITY - Meni Fuzi Astuti Tanjung (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
In general, our society underestimates diarrhea, so that it often has fatal consequences in terms of handling sufferers, this is caused by the application of the principles of rehydration as early as possible has not been implemented by the community resulting in delays in rehydration measures which can exacerbate pain, can even result in death so the researcher took the title The Relationship between Knowledge of Mothers under Toddlers and Handling Diarrhea in Toddlers at the Mayor Umar Damanik Health Center in 2021. The purpose of this study was to see the relationship between the knowledge of mothers who have toddlers and the incidence of diarrhea experienced by toddlers. This research method uses a descriptive correlation method with a cross sectional approach. The population in this study were all mothers with toddlers who had 61 children under five. The results in research on the relationship between the knowledge of mothers who have toddlers, with the incidence of diarrhea at the Public Health Center Major Umar have sufficient knowledge of 33 people (54.0%). The results of the chi-square test show that the significant value of the probability of knowledge is p <0.05 (0.000), meaning that there is a relationship between mother's knowledge and the incidence of diarrhea in toddlers. higher if knowledge about diarrheal disease in mothers is lacking. Author's suggestion It is hoped that health workers can improve their health services in health education about diarrhea in mothers.